2016
DOI: 10.1017/s0032247416000218
|View full text |Cite
|
Sign up to set email alerts
|

Securing sustainability: the case for critical environmental security in the Arctic

Abstract: The politics, economies, and ecology of the Arctic region are experiencing fundamental transformation driven largely by human-caused environmental change. Drawing on the work of Robert Cox, this article presents a critical account of environmental security that allows security issues in the Arctic to be reconceptualised. It outlines the environmental changes transforming the Arctic, and theorises the Arctic as a regional environmental security complex in which conditions of security for state and non-state ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…On the other hand, this study demonstrated that increase in a proportion of traditional food in a diet might have a positive effect on decrease of nutritional disorders and diseases of digestive system in Type 3 and Type 4 territories only, while in the environmentally polluted Type 1 and 2 territories, both consumption of traditional food and hunting/fishing had negative effects on health. This finding supports the results of previous studies by Vinokurova (2011), Greaves (2016) and Ignateva (2018) who all concluded that pollution had threatened the diets and health in the Russian Arctic.…”
Section: Discussion and Fns Implicationssupporting
confidence: 92%
“…On the other hand, this study demonstrated that increase in a proportion of traditional food in a diet might have a positive effect on decrease of nutritional disorders and diseases of digestive system in Type 3 and Type 4 territories only, while in the environmentally polluted Type 1 and 2 territories, both consumption of traditional food and hunting/fishing had negative effects on health. This finding supports the results of previous studies by Vinokurova (2011), Greaves (2016) and Ignateva (2018) who all concluded that pollution had threatened the diets and health in the Russian Arctic.…”
Section: Discussion and Fns Implicationssupporting
confidence: 92%
“…Inequalities often lie within the structures of formal institutions and informal social practices. Applying the concept of human security with an intersectional analysis-that is, examining how law and governance can contribute to inequalities depending on combinations of gender, race, ethnicity, sexual orientation, class, etc.-can be a useful framework for understanding the nature of security threats in the circumpolar Arctic, including the impacts of climate change [25][26][27][28]. For example, changes in the Arctic often result in insecurity and vulnerability of social and ecological systems, which are often rooted in marginalisation of northern populations through colonisation and continued oppression of Arctic Indigenous Peoples [29].…”
Section: Resultsmentioning
confidence: 99%
“…Though, in the authors' point of view, the complex solution to the problems of Arctic development should be associated with the creation of priority development pivot zones in these districts; the implementability of innovative capacity of the territory should be the most crucial issue in such zones. [2][3][4][5][6][7][8][9][10][11] In order to perform this task, it is necessary to fulfil a set of conditions.…”
Section: Resultsmentioning
confidence: 99%